Impact of dietary protein levels and feeding regimes on growth performance and biochemical profile of European sea bass (Dicentrarchus labrax) reared in a brackish water recirculating aquaculture system - Sameh Nasr-Eldahan; Mahmoud A.O. Dawood; Muziri Mugwanya; Fahad Kimera; Hani Sewilam (Aquaculture Reports)
A 16-week trial was conducted to assess the effects of dietary protein levels and feeding regimes on the growth performance and biochemical profile of European sea bass (Dicentrarchus labrax), initial weight 56 ± 1.0 g reared under brackish water conditions (7 ppt) in a recirculating aquaculture system. The experiment was designed as a completely randomized layout of six duplicated treatments: T1 (42 % protein, fed once daily), T2 (42 % protein, fed twice daily), T3 (42 % protein, fed thrice daily), T4 (44 % protein, fed once daily), T5 (44 % protein, fed twice daily), and T6 (44 % protein, fed thrice daily). Our results indicated improved growth performance regarding the feed conversion ratio and specific growth rate in T2 compared to the other treatments. Weight gain was significantly higher in T2, T4, T5, and T6 than in T1 and T3. Additionally, T2 and T4 achieved the highest survival percentages compared to the other treatments. For fish health assessment, our findings revealed significantly lower metabolic enzyme activity of alanine transaminase in T2 and T4 compared to the different treatments, and alkaline phosphatase activity in T2 and T3 compared to T4, T5, and T6. However, T1 recorded significantly the lowest values for aspartate transaminase activity. Regarding kidney function, significantly lower and higher values for glucose, uric acid, and hemoglobin, respectively, were noted in T2. In conclusion, feeding Dicentrarchus labrax with 42 % protein twice daily is an optimal feeding strategy for enhancing its growth performance and health status in brackish water (7 ppt) conditions within a recirculating aquaculture system.